Remote laboratory trends for Distance Vocational Education and Training (D-VET): A real-time lighting application - EKREN, NAZMİ; POLAT, ZÜHAL (SAGE PUBLICATIONS LTD, 2022)
This research presents a web-based lighting laboratory infrastructure that allows students to access and control application tools in lighting technology education through online real-time equipment. Designed for Distance Vocational Training and Education, this system uses the LabVIEW Virtual Instrumentation Program to control lighting levels. In this program, the interface developed allows students to control and monitor applications online using cameras, sensors, and controllers. In the modeled system, the lighting levels of LED lamps are controlled through PID controllers. Furthermore, a web page was designed that provides synchronized (simultaneous) access to application instrumentation for the students. Each user can run applications in a specific period through this website. Students can also monitor the lighting level of the laboratory in real-time with a webcam. Individual storage of the data obtained in the model also supports conducting necessary analyses. Students can strengthen their theoretical knowledge by running lighting technique experiment applications with real equipment in the Distance Vocational Training and Education. In the evaluation part of the research, the answers are given by the students (95%) also stated that they increased the theoretical knowledge of doing remote experiments. In total 98.5% of students believe that the ability to repeat experiments anywhere in this system will accelerate the learning process.
Keywords: Remote laboratory; web-based laboratory; LabVIEW; Distance Vocational Education and Training (D-VET); lighting; TECHNOLOGY; DESIGN